ROLL MOTION CHARACTERISTICS OF SHIP WITH LARGE BREADTH AND DRAUGHT RATIO IN FOLLOWING WAVES - Paroka, Daeng; Asri, Syamsul (Diponegoro University, 2013)
Since the International Maritime Organization decided to revise its intact stability criteria from deterministic based criteria to be performance based one, some researches regarding the ship performance in waves have been conducted by several researches. One of the dangerous condition reccomended to be included in the criteria was the stability of ships in following waves especially for ship with small coefficient for vertical well-sidedness. Ships with large breadth and draught ratio tends to have large the coefficient for well-sidedness. However large roll angle may occur when the ships operate in large significant wave height. The forward speed also could have significant effect on the roll motion characteristics due to time spend of ship in a certain position relative to the wave. This paper discusses effect of restoring arm variation due to waves characteristics and ship speed on roll motion of ships with large breadth and draught ratio in following waves. The waves characteristics is modelled based on the Beaufort scale and the forward speed is estimated by changing the propeller revolution from 6 rps to 15 rps. The results of numerical simulation and discussions show that amplitude of roll motion significantly affected by variation of the waterline area of the ship in sugging and hogging condition. The large roll angle can be avoided by increasing the forward speed with considering the other dangerous condition such as pure loss of stability and broaching.